Effect Of Post Processing Parameters Andcompression Behavior On FDM 3D-Printed ABS Lattice-Structures - Rosli, Nur Ameelia (2019)
There is a growing development in lattice structure due to fundamental interest of the industries in producing parts with higher performance albeit with a low energy and cost consumption. Lattice structure is a periodic cellular structure which can serve the purpose of achieving lightweight parts with good mechanical properties. The complexity of manufacturing numerous types of lattice structures can be overcome by additive manufacturing (AM) process which offers better reliability and relatively simple procedure as compared to normal manufacturing. For the past decade, there are many studies on the lattice structure fabrication by AM. However, from literature, it is found that not many studies reported about the investigation on lattice structure by non-metallic, especially the ABS polymer. The use of ABS polymer to produce lattice structure serves as an added value for lightweight applications due to the lightweight characteristics of the ABS itself. The fused deposition modeling (FDM) 3D printed process of lattice structure is rarely reported in previous studies, hence it is difficult to confidently understand the behaviour of produced lattice structure by using combinations of FDM parameters. On top of that, there is limited information regarding the relationships between the pre-set parameters of CubePro’s mid- range FDM printed lattice structure with its mechanical properties. Therefore, this study characterized and examined the manufacturability of lattice structure geometry that was produced by FDM. The effect of process parameters of mid-range FDM 3D printer on the geometry of ABS lattice-structure were then evaluated. Later, the relationships between mechanical properties of ABS FDM 3D printed lattice structure with its geometry were derived by using experimental approach to justify the material as lightweight material. The CubePro 3D printer machine was utilized to fabricate the BCC lattice structure cube specimens with dimension of 20 x 20 x 20 mm3 with strut’s diameter sizes of 1.2 mm, 1.4 mm and 1.6 mm. Optical microscopy was used to characterize the printed lattice structures cube specimens. Theoretical approach was performed to compare the results with previous studies. The lattice structures specimens were tested with quasi-static compression loading to examine its mechanical properties and then the relations between process-properties of FDM 3D printed lattice-structure were derived. The significant process parameters that influenced the mechanical performance as well as the geometrical properties for this particular FDM printer machine was found to be the layer thickness. The best mechanical performance of lattice structure was observed for that produced with 200 µm layer thickness as it gave a good agreement between the theoretical approach and experimental data analysis. With respect to the deformation behavior of the lattice structure in this study, the material is found to be more suitable in energy absorption applications such as in car engine hood or arm parts of the drone due to the bending dominated behavior when subjected to loading.